Optimal routing for electric vehicle macro-groups in urban areas: Application to the city of Santiago, Chile - De-la-Torre-Fazio, Sebastián Bienvenido; Aguado-Sánchez, José Antonio; Sauma, Enzo; Lozano-Martos, Alejandro (Elsevier, 2024)
With increasing penetration of Electric Vehicles (EVs) and growing interest in Vehicle to Grid (V2G) technology, the route optimization problem for EVs and the interaction with the power grid is becoming a more relevant research topic. We aim to optimize the route selection and charging/discharging patterns to improve the overall economic profits of EVs, considering time-varying energy prices, location of charging infrastructure and traveling schedules for EVs. We propose an optimization-based approach for EV routing where vehicles may recharge on- the-route at public charging infrastructure as well as at privately-owned depots. The objective function considers charging/discharging strategies under both, net billing and net metering tariff schemes. We also study some emerging technological solutions, such as autonomous vehicles, that can introduce more flexibility to the system operations. The proposed approach is evaluated using an origin-destination survey and the real traffic map around Santiago, Chile. Our results show that, while most EVs made minimum-distance home-work trips, it is optimal for some EVs to make additional trips to charge at cheaper nodes or inject at more expensive nodes, resulting in significant profit variations. Additionally, different values of charger availability influence total profit, resulting in profit fluctuations of up to 2 % in our case study.
Keywords: Vehículos eléctricos; Sistemas de comunicaciones inalámbricos; Electric vehicle aggregator; Vehicle to grid; Electric vehicles; Smart charging; EV routing; Autonomous vehicles